2017
DOI: 10.3390/toxins9040140
|View full text |Cite
|
Sign up to set email alerts
|

Toxins of Prokaryotic Toxin-Antitoxin Systems with Sequence-Specific Endoribonuclease Activity

Abstract: Protein translation is the most common target of toxin-antitoxin system (TA) toxins. Sequence-specific endoribonucleases digest RNA in a sequence-specific manner, thereby blocking translation. While past studies mainly focused on the digestion of mRNA, recent analysis revealed that toxins can also digest tRNA, rRNA and tmRNA. Purified toxins can digest single-stranded portions of RNA containing recognition sequences in the absence of ribosome in vitro. However, increasing evidence suggests that in vivo digesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 162 publications
0
37
0
Order By: Relevance
“…Transcriptome and proteome data of M. mazei indicate co-expression of HARP (Mm_2077) and RNA-based RNase P subunits (Mm_1556 = Rpp21, Mm_2132 = Rpp29, Mm_2618 = Rpp30, Mm_2619 = Pop5, Mm_2467 = L7Ae) (unpublished data). The HARPs are evolutionarily linked to toxin-antitoxin systems in bacteria and archaea (20), where the toxin proteins are often sequence-specific endoribonucleases that degrade mRNA, rRNA, tmRNA or tRNA to inhibit protein biosynthesis in response to certain stresses (28). For example, proteins with a PIN domain-like fold of the VapC (virulence-associated protein C) type include VapC endonucleases from Shigella flexneri and Salmonella enterica Typhimurium LT2 that specifically cleave initiator-tRNA fMet (but not elongator tRNAs including tRNA Met ) in the anticodon loop at the junction to the 3 0 -strand of the anticodon stem (29).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome and proteome data of M. mazei indicate co-expression of HARP (Mm_2077) and RNA-based RNase P subunits (Mm_1556 = Rpp21, Mm_2132 = Rpp29, Mm_2618 = Rpp30, Mm_2619 = Pop5, Mm_2467 = L7Ae) (unpublished data). The HARPs are evolutionarily linked to toxin-antitoxin systems in bacteria and archaea (20), where the toxin proteins are often sequence-specific endoribonucleases that degrade mRNA, rRNA, tmRNA or tRNA to inhibit protein biosynthesis in response to certain stresses (28). For example, proteins with a PIN domain-like fold of the VapC (virulence-associated protein C) type include VapC endonucleases from Shigella flexneri and Salmonella enterica Typhimurium LT2 that specifically cleave initiator-tRNA fMet (but not elongator tRNAs including tRNA Met ) in the anticodon loop at the junction to the 3 0 -strand of the anticodon stem (29).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we revealed that the MazF toxin (MazF DR0417 ) functions as a 4‐nt specific cutter and strictly recognizes the UACA tetrad (Figures ). To the best of our knowledge, this is the first MazF that specifically recognizes the U^ACA sequence (Masuda & Inouye, ; Schifano & Woychik, ). Recently, Zorzini et al., () determined the crystal structure of E. coli MazF (MazFec) in complex with the substrate analogue d(A 1 U 2 A 3 C 4 A 5 U 6 A 7 ), and reinforced the notion that MazFec recognizes ACA triplet strictly and that MazFec cleaves the substrate at the position of ^ACA and A^CA (Miyamoto et al., ; Vesper et al., ; Zhang, Zhang, Hara, Kato, & Inouye, a; Zhang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we revealed that the MazF toxin (MazF DR0417 ) functions as a 4-nt specific cutter and strictly recognizes the UACA tetrad (Figures 2-4). To the best of our knowledge, this is the first MazF that specifically recognizes the U^ACA sequence (Masuda & Inouye, 2017;Schifano & Woychik, 2017 (Miyamoto et al, 2016a;Vesper et al, 2011;Zhang, Zhang, Hara, Kato, & Inouye, 2005a;Zhang et al, 2003). They mentioned that the MazFec recognition site could be divided into two different regions: first, the one where dU 2 is located, which is called the upstream binding site; and second, the one that accommodates d(A 3 C 4 A 5 U 6 ), which is called the downstream binding groove.…”
Section: Discussionmentioning
confidence: 99%
“…In the type II TA system, two protein genes (toxin and antitoxin) are co-expressed (14, 15). In normal conditions, antitoxin inhibits the activity of the stable toxin by forming a tight proteinprotein complex (16). In the stress condition, the labile antitoxin is selectively degraded by cellular proteases such as Lon and clpXP.…”
Section: Introductionmentioning
confidence: 99%